Mastering Geospatial Development with QGIS 3.x : An in-depth guide to becoming proficient in spatial data analysis using QGIS 3.4 and 3.6 with Python, 3rd Edition /: An in-depth guide to becoming proficient in spatial data analysis using QGIS 3.4 and 3.6 with Python, 3rd Edition. (2019) - Islam, Shammunul; Miles, Simon; Pirelli, Luigi
No abstract available